Advancing paternal age and risk of autism: new evidence from a population-based study and a meta-analysis of epidemiological studies - Hultman, C M; Sandin, S; Levine, S Z; Lichtenstein, P; Reichenberg, A (Molecular psychiatry, 2011)
Advanced paternal age has been suggested as a risk factor for autism, but empirical evidence is mixed. This study examines whether the association between paternal age and autism in the offspring (1) persists controlling for documented autism risk factors, including family psychiatric history, perinatal conditions, infant characteristics and demographic variables; (2) may be explained by familial traits associated with the autism phenotype, or confounding by parity; and (3) is consistent across epidemiological studies. Multiple study methods were adopted. First, a Swedish 10-year birth cohort ( N =1 075 588) was established. Linkage to the National Patient Register ascertained all autism cases ( N =883). Second, 660 families identified within the birth cohort had siblings discordant for autism. Finally, meta-analysis included population-based epidemiological studies. In the birth cohort, autism risk increased monotonically with increasing paternal age. Offspring of men aged ⩾50 years were 2.2 times (95% confidence interval: 1.26–3.88: P =0.006) more likely to have autism than offspring of men aged ⩽29 years, after controlling for maternal age and documented risk factors for autism. Within-family analysis of discordant siblings showed that affected siblings had older paternal age, adjusting for maternal age and parity ( P <0.0001). Meta-analysis demonstrated advancing paternal age association with increased risk of autism across studies. These findings provide the strongest evidence to date that advanced paternal age is a risk factor for autism in the offspring. Possible biological mechanisms include de novo aberration and mutations or epigenetic alterations associated with aging.